Modeling and analysis of pelletization process based on a multi-hole pelletizing device - Jiang, Qinghai; Wu, Kai; Sun, Yu (International Journal of Agricultural and Biological Engineering, 2019)
A multi-hole pelletizing device (MPD) was proposed to simulate the granular extrusion process of animal feed due to its cheap, fast, and controllable features. The compression mechanism was analyzed and discussed according to the compression force-time curve. This study applied response surface methodology (RSM) with a central composite design (CCD) to develop predictive models for the compression force Fout and the pellet properties which includes pellet density ρp, pellet moisture content Mcp, and pellet tensile strength Dp based on the MPD. The effects of feedstock moisture content Mcf (10%-18% w.b.), feedstock particle size Sf (8 meshes -24 meshes), die temperature Td (70°C-110°C) and compression speed Vc (5 mm/min to 25 mm/min) were investigated. Response surface models developed for the compression force and pellet properties have adequately described the pelleting process (R2 >0.95). The results showed the significant effects of all factors and most of the squared and interaction terms on the compression force and pellet physical properties. It can be concluded from the present study that moisture content and die temperature, followed by compression speed and feedstock particle size are the interacting process factors influencing compression force and pellet properties.Keywords: animal feed, pelletization, modeling, compression force, response surface methodology, analysis of varianceDOI: 10.25165/j.ijabe.20191201.3264Citation: Jiang Q H, Wu K, Sun Y. Modeling and analysis of pelletization process based on a multi-hole pelletizing device. Int J Agric & Biol Eng, 2019; 12(1): 17–23.